Book Reviews - Reeves , Andrew; Moore , Peter; Shapley , Maggie; Sissons , D.C.S.; Pemberton , Pennie (Archives & Manuscripts, 1983)
C.J. Jones. Britain and the Dominions: a guide to business and related records reviewed by Andrew Reeves; Register of Church archives. A select guide to resource material in Australia reviewed by Peter Moore; Queensland State Archives. Guide to the records of the Lands Department 1866-1910 reviewed by Maggie Shapley; W.J. Hudson and H.J.W. Stokes. Eds Documents on Australian foreign policy 1937-49, Vol. V reviewed by D.C.S. Sissons; David Saunders Ed. A manual of architectural history sources Vol 1 and Vol 2 reviewed by Pennie Pemberton